1989
DOI: 10.1104/pp.90.2.635
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Sucrolysis via the Uridine Diphosphate and Pyrophosphate-Dependent Sucrose Synthase Pathway

Abstract: The breakdown of sucrose to feed both hexoses into glycolytic carbon flow can occur by the sucrose synthase pathway. This uridine diphosphate (UDP) and pyrophosphate (PPi)-dqpendent pathway was biochemically characterized using soluble extracts from several plants.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
56
1

Year Published

1990
1990
2013
2013

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 95 publications
(59 citation statements)
references
References 25 publications
2
56
1
Order By: Relevance
“…It is the predominant sucrose cleavage enzyme in cereal endosperm and in storage organs such as tubers, fruits, seed or immature leaves [24,28]. Sucrose synthase in these carbohydrate sink organs provides substrates for respiration [29], 586 R. Le Hir et al…”
Section: Introductionmentioning
confidence: 99%
“…It is the predominant sucrose cleavage enzyme in cereal endosperm and in storage organs such as tubers, fruits, seed or immature leaves [24,28]. Sucrose synthase in these carbohydrate sink organs provides substrates for respiration [29], 586 R. Le Hir et al…”
Section: Introductionmentioning
confidence: 99%
“…The first hypothesis has been favored by several groups (2,8,24), who considered that the role of the reaction is to provide PPi Fru-2,6-P2, fructose 2,6-bisphosphate; Fru-6-P, fructose 6-phosphate; PPi, inorganic pyrophosphate; Glc-6-P, glucose 6-phosphate.…”
mentioning
confidence: 99%
“…Inorganic nitrogen could do this by diverting triose phosphates out of the pentose phosphate reductive cycle, thus exercising substrate limitation for starch and sucrose synthesis. A second possibility is that one or more enzymes involved in starch and/or sucrose biosynthesis or its degradation are influenced by N2 fixation and/or inorganic nitrogen supply (17,31,38) (CC Black, private communication). For example, Kerr et al (17) found that the activity of ADPG-PPiase, the principal rate limiting starch synthesis pathway enzyme, was slightly lower in soybean leaves of NO3-fed plants compared to leaves from N2-fixing plants.…”
Section: Maintenance Of Photosynthetic Rate In Nod+/-source Leaves Tomentioning
confidence: 99%